About the Legal Phenomenon of Administrative Simplification, ¿Facility or Restriction? - Bueno Junquero, Adrián (EUNOMÍA. Revista en Cultura de la Legalidad, 2019)
The present essay intends to explore the normative and reflexive dimensions of the administrative simplification phenomenon. For this purpose, it exposes a triad of elements –normative, organic and procedural– that leads to an investigation about the normative dispositions which regulates the phenomena as well as opens the door to a philosophical and legal reflexion about its two levels: (1) normative moment; (2) legal subjectivity moment. Finally, it concludes with the presentation of the triad from a double perspective in order to enable the thinking of graduality within the framework of mandatory legality.